We are at war! - Oliveira, Gabriela Clemente de (Revista do Colóquio, 2024)
This visual essay is part of an action that aims to promote encounters between art images and video content available on YouTube to build, from groupings, new aesthetic bodies, other images. Why include YouTube in a creative process? Because it is a platform inhabited by extensive visual material and easy access. Pellegrini; Reis; Monção and Oliveira (2010) highlighted that the YouTube platform functions as a bank of audiovisual products where image and sound complement each other with simplicity. A tool for the dissemination of images and the most diverse discourses, a “food for an audience that yearns to represent itself” (Pellegrini; Reis; Monção; Oliveira, 2010, p.3). The principle that drives this action of combining art images and material available on video platforms is that of montage. Carone (1973), in the exercise of trying to define montage, in the field of arts, pointed out that it is an activity that unites strange elements in the same body. What links these different elements in the same space is the spectators’ emotions and reasoning. Carone (1973) revisited Eisenstein to broaden understanding. For the Russian filmmaker, montage is an action of mental fusion or synthesis, “in which isolated details (fragments) come together, at a higher level of thought, in an unusual way, (...) different from the common logical form” (Carone, 1973, p.4). The images that make up this study are montages that were born, in a simple and direct way, from the encounter between the first episode of the documentary Wars of Brazil (2020), especially Ailton Krenak’s speeches, and reproductions of Jean Baptiste Debret’s watercolors available in the material O Brasil de Debret (1993). The images used in the work were: Plate nº1 - Camacã Indian - Mongoio; Plate nº2 - Camacã Indian; Plate nº20 - Indian soldiers from Curitiba, escorting savages; Plate No. 26 - Virgin forests of Brazil, on the banks of the Paraíba River; Plate No. 63 - Tiger hunting; Plate No. 85 - Fruits of Brazil; Plate No. 92 - Disembarkation of the royal princess Leopoldina; Plate No. 100 - Acclamation of Dom Pedro, Emperor of Brazil. Watching the documentary evoked images produced by the artist and painter who was part of the French artistic mission in the 19th century. The encounter between Ailton Krenak's speeches and Debret's work caused tension.